DNA methylation inhibitors adverse reaction characteristic analysis: a descriptive analysis from WHO-VigiAccess - Zhou, Qiang; Xie, Quanlei; Liu, Qiang; Wang, Haojie; Zhang, Zhan; Yu, Zhao; Guo, Qian; Lin, Jie (Frontiers in Pharmacology, 2024)
Introduction：DNA methylation inhibitors (azacitidine, decitabine) have revolutionized the treatment dilemma of myelodysplastic syndromes (MDS), a group of malignant hematopoietic disorders. This study evaluates the adverse drug reactions (ADRs) following the use of DNA methylation inhibitors in the World Health Organization (WHO) VigiAccess database and compares the characteristics of ADRs between the two drugs to select the drug with the minimum individualized risk for patients.Methods: This study employed a retrospective descriptive analysis method. We compiled ADR reports for two marketed DNA methylation inhibitors for the treatment of MDS from WHO-VigiAccess. Data collected included demographic data such as age groups, gender, and regions of global patients covered by ADR reports, as well as data on the disease systems and symptoms caused by ADRs recorded in the annual reports and reports received by WHO. By calculating the proportion of ADRs reported for each drug, we compared the similarities and differences in ADRs between the two drugs.Results: Overall, 23,763 adverse events (AEs) related to the two DNA methylation inhibitors were reported in VigiAccess. The results showed that the top 10 most common AEs were febrile neutropenia, bone marrow suppression, neutropenia, anemia, pancytopenia, leukopenia, thrombocytopenia, bone marrow failure, agranulocytosis, and hematotoxicity. The top five common types of DNA methylation inhibitor AEs were blood and lymphatic system disorders (11,178 cases, 47.0%), cardiac organ diseases (1,488 cases, 6.3%), various congenital familial genetic diseases (49 cases, 0.2%), ear and labyrinth diseases (100, 4.2%), and endocrine system diseases (57, 2.4%).There is no Strong correlation between DNA methylation inhibitors and ADRs.Current comparative observational studies of these inhibitors show that there are common and specific adverse reactions in the ADR reports received by WHO for these drugs. Clinicians should improve the rational use of these drugs based on the characteristics of ADRs.